2022
DOI: 10.1088/1755-1315/976/1/012022
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in carbon dioxide and methane production of tropical peatlands due to coal fly-ash application

Abstract: Tropical peatlands with very high organic carbon (C) contents have the potential to be a source of carbon dioxide (CO2) and methane (CH4) production. Therefore, the management of tropical peatlands is essential to prevent peat decomposition and to reduce the production of CO2 and CH4. We added different amounts of coal fly-ash (CFA) (0, 25, 50, 75, 100 and 125 Mg ha−1) to tropical peats in a laboratory study to quantify changes in CO2 and CH4 production in response to the application of CFA. The amounts of CO2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…A low amount of hot-water soluble C with application of CFA reduced the amount of the C for microbial decomposition to produce CO 2 . Furthermore, the result of a previous study showed a low CO 2 and CH 4 production results from a reduction in the amount of hot-water soluble C in peatlands with CFA addition (Saidy et al, 2022).…”
Section: Effect Of Cfa On Carbon Mineralization Of Peatlands With Nit...mentioning
confidence: 93%
See 1 more Smart Citation
“…A low amount of hot-water soluble C with application of CFA reduced the amount of the C for microbial decomposition to produce CO 2 . Furthermore, the result of a previous study showed a low CO 2 and CH 4 production results from a reduction in the amount of hot-water soluble C in peatlands with CFA addition (Saidy et al, 2022).…”
Section: Effect Of Cfa On Carbon Mineralization Of Peatlands With Nit...mentioning
confidence: 93%
“…This adsorbed organic C is resistant to microbial decomposition processes (Sowers et al, 2018;Liu et al, 2019). Prior examinations also showed that application of CFA reduces the substrate availability for microorganisms, therefore it produces low carbon mineralization in organic soils (Saidy et al, 2022) and mineral soils (Lim and Choi, 2014;Lim et al, 2017;Saidy et al, 2020).…”
Section: Effect Of Cfa On Carbon Mineralization Of Peatlands With Nit...mentioning
confidence: 99%